(untitled) (Journal of the College of Basic Education, 2022)
Pragmatics and Semantics are inter-related subjects and the distinction between them is necessary to provide a framework for explaining the variety of ways in which what a speaker conveys can fail to be fully determined by the (conventional) linguistic meaning of the sentence he utters. In a more positive vein, the distinction between semantics and pragmatics has served to separate strictly linguistic facts about utterances from those that involve the actions, intentions, and inferences of language users (speaker- hearers). However, there are some linguistic phenomena that seem to straddle the semantics-pragmatics boundary.